Analysis of Controlling Wireless Temperature Sensor for Monitoring Peat-Land Fire - Marpaung, Noveri Lysbetti; Amri, Rahyul; Ervianto, Edy; Dani Ali, Nurhalim (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2018)
The problem of forest and peatland fires in Riau has become main topic to prioritize its revamping. Land and forest fires in Riau until reached 3,700 hectares area, happened in some last years,.Forest and peatland fires occured in the majority of districts in Riau Province, from low category of 4 hectares until 2,800 hectares. This researchdiscusses aboutanalysis of controlling wirelessTemperature Sensor for monitoring Peat-Land fire by using LM35 Temperature Sensor, Transmitter-Module (HC-12), Receiver-Module (HC-12), Arduino-ProMini to produce outputs on LED, LCD, Buzzer. Detector of Peat-Land fire works when it is burning, so heat will spread through aluminium stalk and be read by Temperature-Sensor1 upto Temperature-Sensor4. Output of each sensor is sent to each control block of Arduino-ProMini in Transmitter-Module(FU1–FU4). From Arduino-ProMini, it is sent toReceiver-Module(FU5). Receiver-Module only receives one data from Transmitter-Module in one time. Every data is received by Receiver-Module goes to Arduino-ProMini, processed to produce outputs on LCD that shows ID of FU1–FU4, Peat-Land Status, temperature of Peat Land. If LED is Green, Peat-Land not burned, LED shows SAFE Condition, Buzzer Off. If LED is Yellow, Peat-Land burned underground, LED shows BE-CAREFUL Condition, Buzzer On. If LED is Red, Peat-Land burned on the ground, LED shows DANGER Condition, Buzzer On. Temperature 0°C–21.9°Cis SAFE Category because Peat-Land not burned. Temperature 22°C–28.4°Cis BE-CAREFUL Category because Peat-Land burned underground. Temperature 28.4°C–50°Cis DANGER Category because Peat-Land burned on the ground. This equipment works as its frame work.